1990
DOI: 10.2166/wst.1990.0018
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality of the Danube in Hungary and its Major Determining Factors

Abstract: Three District Water Authorities cover the whole Hungarian stretch of the Danube. Since the formation of the monitoring network fifteen years ago, the water quality has been observed at fifteen sampling points. Throughout this time, sampling has been performed under different hydrometeorological conditions. Based on these investigations, it was found that the quality of the river was influenced equally by the local and the hydrometeorological conditions. Major pollution sources are: the sewage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the other measurement points of Marcal, where red mud is not present in appreciable quantities, toxicity remains under 20%, with gypsum dosing having no noticeable effect compared to reference samples. The high toxicity in the R aba (R2) and Mosoni-Duna (MD1) samples is most likely a diffuse pollution signal from decades of industrial activity and municipal sources in the area of Gy} or city, 41 which may include organic contaminants not measured here. There are highly significant positive correlations between Lemna minor inhibition rate and exchangeable Na (rs ¼ 0.69, p ¼ 0.002), Co, Cr, Fe and Ni (rs between 0.70 and 0.75; p < 0.001; Fig.…”
Section: Lemna Minor Leaf Reproduction Inhibition Testmentioning
confidence: 97%
“…In the other measurement points of Marcal, where red mud is not present in appreciable quantities, toxicity remains under 20%, with gypsum dosing having no noticeable effect compared to reference samples. The high toxicity in the R aba (R2) and Mosoni-Duna (MD1) samples is most likely a diffuse pollution signal from decades of industrial activity and municipal sources in the area of Gy} or city, 41 which may include organic contaminants not measured here. There are highly significant positive correlations between Lemna minor inhibition rate and exchangeable Na (rs ¼ 0.69, p ¼ 0.002), Co, Cr, Fe and Ni (rs between 0.70 and 0.75; p < 0.001; Fig.…”
Section: Lemna Minor Leaf Reproduction Inhibition Testmentioning
confidence: 97%
“…Thus an important element in preventing and controlling river pollution by an effective management of STP is the existence of reliable and accurate information about the concentrations of pollutants in wastewater. Studies of wastewater in Danube basins can be found, for instance, in central and eastern European countries [ 13 15 ], but we are not aware of extensive studies of wastewater quality at regional/national level in Romania.…”
Section: Introductionmentioning
confidence: 99%
“…In the sediment the heavy metal concentrations were much higher (100...1 000 times) than in the water [11,12]. Presumably sediment works as a trap for heavy metals, in the form of highly insoluble sulfides.…”
Section: Resultsmentioning
confidence: 99%